The Study of Mechanical Failure in Helical Steam Generator of High Temperature Gas-Cooled Reactor (HTGR) - Subhan, Muhammad; Setiadipura, Topan; Purwadi, Mohammad Dhandhang; Setiawan, Muksin Aji; Soemardi, Tresna Priyana; Baskoro, Aryo Sunar; Abadi, Cecep Slamet; Latifah, Evi; Amalia, Nafisah; Renaningtyas, Yusi Amalia (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
This research examines mechanical damage in helical steam generators, focusing on the causes, contributing factors, and impact of damage on the performance of the steam generator (SG). The research methodology involves analyzing various data sources, including scientific literature and previous nuclear industry experiences. The analysis results indicate that thermal stress, pressure fluctuations, material wear, and design errors can cause mechanical damage in helical SGs. Volumetric defects and leaks at pipe joints or welds are also potential issues. This study provides insights into failure mechanisms and highlights the importance of routine maintenance and inspection to prevent more serious failures. By better understanding these issues, innovative solutions can be developed to improve the performance and safety of helical steam generators in nuclear reactors.